2011
DOI: 10.1021/bi201019n
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Viral Sialidases: Contribution of the Conserved Active Site Glutamate to Catalysis

Abstract: Mutagenesis of the conserved glutamic acid of influenza type A (E277) and Micromonospora viridifaciens (E260) sialidases was performed to probe the contribution of this strictly conserved residue to catalysis. Kinetic studies of the E260D and E260C M. viridifaciens mutant enzymes reveal that the overall mechanism of action has not changed. That is, the mutants are retaining sialidases in which glycosylation and deglycosylation are rate-limiting for k(cat)/K(m) and k(cat), respectively. The solvent kinetic isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Bacterial sialidases are classified in glycosyl hydrolase family 33 and their structures are of the six-bladed β-propeller type (Crennell et al, 1993). As retaining glycosidases, they employ a double-displacement mechanism and use a Tyr residue as catalytic nucleophile (Watts et al, 2003) while a conserved Asp-Glu pair is involved in general acid/base catalysis (Chan et al, 2012). Interestingly, this enzyme can retain function upon mutation of either of the catalytic residues (D92, E260 and Y370) (Watson et al, 2003;Chan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial sialidases are classified in glycosyl hydrolase family 33 and their structures are of the six-bladed β-propeller type (Crennell et al, 1993). As retaining glycosidases, they employ a double-displacement mechanism and use a Tyr residue as catalytic nucleophile (Watts et al, 2003) while a conserved Asp-Glu pair is involved in general acid/base catalysis (Chan et al, 2012). Interestingly, this enzyme can retain function upon mutation of either of the catalytic residues (D92, E260 and Y370) (Watson et al, 2003;Chan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Retaining NA mechanisms, on the other hand, appear to be quite distinct. Biochemical analysis of NA from various microorganisms has revealed that a conserved active-site tyrosine can function as a nucleophile and may be the most important catalytic residue [17][18][19] .…”
mentioning
confidence: 99%
“…However, the viral and bacterial NA enzymes, all belonging to clan GH‐E, contain a sixfold β‐propeller as the prominent structural motif, and the release of progeny virus particles from infected host cells requires the presence of the exo‐sialidase composed commonly of three acidic amino acids, a tyrosine, and three arginines (Chan et al . ). In view of the highly conserved active site of the target enzymes of the viral and bacterial origin (Chan et al .…”
Section: Discussionmentioning
confidence: 97%
“…In view of the highly conserved active site of the target enzymes of the viral and bacterial origin (Chan et al . ), the three characterized NA inhibitors are of value in terms of drug discovery for the treatment of viral infections such as influenza.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation